Quantitative investigations of the epidemiology of phocine distemper virus (PDV) in European common seal populations - Grenfell, B. T.; Lonergan, M. E.; Harwood, J. (Science of The Total Environment, 1992)
This paper uses simple mathematical models to examine the long-term dynamic consequences of the 1988 epizootic of phocine distemper virus (PDV) infection in Northern European common seal populations. In a preliminary analysis of single outbreaks of infection deterministic compartmental models are used to estimate feasible ranges for the transmission rate of the infection and the level of disease-induced mortality. These results also indicate that the level of transmission in 1988 was probably sufficient to eradicate the infection throughout the Northern European common seal populations by the end of the first outbreak. An analysis of longer-term infection dynamics, which takes account of the density-dependent recovery of seal population levels, corroborates this finding. It also indicates that a reintroduction of the virus would be unlikely to cause an outbreak on the scale of the 1988 epizootic until the seal population had recovered for at least 10 years. The general ecological implications of these results are discussed.